ISOLATION OF OIL DEGRADATION BACTERIA FROM SEDIMENT IN SUNGAI PAKNING WATERS OF BENGKALIS REGENCY AND THE ABILITY TO DEGRADE CRUDE OIL - Gina Ulfa Fitria; Nursyirwani Nursyirwani; Thamrin Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Oil pollution in Bengkalis waters usually comes from land, marine transportation, defection port activities and oil industry. Oil pollution can be trapped in sediment because it can not be dissolved and difficult to degrade, one way to overcome pollution is by bioremediation. The purpose of this research was to isolate bacteria from sediment Sungai Pakning waters, to examine the ability of isolates in degrading crude oil and to identify the bacterial isolates genetically based on sequence 16S rRNA. The research was conducted from March to May 2018. Bacterial isolation was conducted in Laboratory of Marine Microbiology and the oil degradation analysis was conducted in Laboratory of Chemical Oceanography, Faculty of Fishery and Marine Science, University of Riau. This research used survey and experiment method, survey method to measuring of water quality, removal of sample and isolated of bacteria, experiment method to examine the ability of isolates in degrading crude oil. The result showed that eight isolates (7D15, 7D35, 7D23, 14D15, 14D34, 21D13, 21D23, 21D35) were able to degrade crude oil at 1-3% concentrations. The highest degradation at 1% concentration was indicated by 21D35 isolate, at 2%  concentration is indicated by  21D13 isolate, and at 3% concentration is indicated by 7D23 isolate. To molecular identification results by the 16S rRNA sequence take of three isolates have the highest degradation ability. 21D13 isolate was similar to Achromobacter pulmonis, 21D35 isolate was similar to Achromobacter sp., and 7D23 isolate was similar to Vibrio sp. Keyword : Pakning River, Oil Degradation Bacteria, 16 rRNA, Achromobacter, Vibrio